Die Frau im neuen bürgerlichen Gesetzbuch : eine Beleuchtung und Gegenüberstellung der Paragraphen des Entwurfs eines bürgerlichen Gesetzbuchs für das Deutsche Reich (2. Lesung) nebst Vorschriften zur Änderung derselben im Interesse der Frauen - Proelss, Sera (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1895)
The significance of the new Bürgerliches Gesetzbuch for German women is illustrated in yet another treatise on its provisions and implications for women. This particular work goes another step, however, in that it also provides suggestions for improving the rough draft of the law before it is passed.